Total joint arthroplasty of the thumb CMC joint - Jurča, Jiří; Vlach, Martin; Havlas, Vojtěch (Archives of orthopaedic and trauma surgery, 2025)
PURPOSE OF THE STUDY: Rhizarthrosis-osteoarthritis of the thumb carpometacarpal (CMC) joint is usually a primary idiopathic disease. Total joint arthroplasty (TJA) is one of the surgical treatment options for symptomatic advanced thumb CMC arthritis. This retrospective study aims to evaluate the mid-term functional and radiological results of TJA with the minimum follow-up period of 3 years after the surgery. MATERIAL AND METHODS: Presented are the results of 136 total trapeziometacarpal joint replacements in the group of 105 patients consisted of 96 women and 9 men. Used prostheses were ELiS® implant (27 cases), Ivory® implant (42 cases), Touch® Dual mobility (67 cases). The follow-up period was minimally 3 years postoperatively. In all the patients, along with range of motion and radiologic evaluation of implant position, the function and pain of operated joint were evaluated using DASH and VAS score at regular intervals pre- and postoperatively. RESULTS: At a mean of 85 months (range 38-126 months) post-operatively, patients in 116 cases (85%) reported full satisfaction and absence of symptoms and difficulties. In 12 cases (9%) some slight residual post-exercise pain was reported. In eight cases (6%) patients suffered from episodic rest-pain, but with a lower intensity than in the preoperative period. Postoperatively, the patients declared subjective improvement in hand function. The total DASH score and VAS score decreased in all patients, while ROM increased. The course of all of TJA surgeries was complication-free. Five patients needed revision surgery. In two patients a dislocation has occurred and in three cases a loosening of the cup's implant was reported. The most frequent postoperative complication was the occurrence of transient paraesthesias of the thumb in eight cases (6%). CONCLUSIONS: TJA is the method of choice in management of advanced symptomatic osteoarthritis of the thumb CMC joint. Mastering surgical technique, TJA represents safe and effective treatment method in advanced degenerative changes of the thumb CMC joint and it's benefits exceed possible perioperative and postoperative risks.
Keywords: karpometakarpální klouby; senioři; protézy kloubů; Thumb; Carpometacarpal Joints; senioři nad 80 let; Osteoarthritis; Retrospective Studies; výsledek terapie; Middle Aged; Total joint arthroplasty; mužské pohlaví; palec ruky; Adult; osteoartróza; Trapezium component; Aged, 80 and over; ženské pohlaví; Thumb CMC joint; retrospektivní studie; Humans; artroplastiky kloubů; lidé středního věku; Joint Prosthesis; Rhizarthrosis; dospělí; rozsah kloubních pohybů; Female; Aged; Arthroplasty, Replacement; Treatment Outcome; Range of Motion, Articular; lidé; Male